Geologic Field Database - Hribernik, Katarina; Šinigoj, Jasna; Komac, Marko; Šajn, Robert; Premru, Uroš (Geologija, 2002)
The purpose of the paper is to present the field data relational database, which was compiled from data, gathered during thirty years of fieldwork on the Basic Geologic Map of Slovenia in scalel:100.000. The database was created using MS Access software. The MS Access environment ensures its stability and effective operation despite changing, searching, and updating the data. It also enables faster and easier user-friendly access to the field data. Last but not least, in the long-term, with the data transferred into the GIS environment, it will provide the basis for the sound geologic information system that will satisfy a broad spectrum of geologists’ needs.